THE ROLE OF WOMEN IN DEVELOPING THE HOUSEHOLD ECONOMY ACCORDING TO ISLAMIC PERSPECTIVE - Khoirul Sya'ban, Tino; Imam Nugroho, M. Nashril (ISTISMAR, 2019)
Often, perspectives on working women raise pros and cons in society. This is due to the stereotype that exists in society that women must be good at taking care of the household and that if a woman works, they are worried that they will not fulfill their household obligations. However, this view has changed in the contemporary era as society's understanding of the role of women in society has grown. By using the library data collection method, this study aims to improve understanding of the role of women in building the household economy. This data comes from the Quran, Hadith, and journals that discuss the role of women and Islamic economics. This data comes from the Quran, Hadith, and journals that discuss the role of women and Islamic economics. This study found that Islam gives permission for women to work as long as the work does not conflict with her naturalness and is permitted by her husband. A woman who works must be able to maintain her honor and divide her role in her work while still paying attention to her household responsibilities.